2018
DOI: 10.1128/aac.02457-17
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Extensively Drug-Resistant or Pandrug-Resistant Sequence Type 147 and 101 OXA-48-Producing Klebsiella pneumoniae Causing Bloodstream Infections in Patients in an Intensive Care Unit

Abstract: Carbapenem-resistant causes important health care-associated infections worldwide. An outbreak of sequence type 11 (ST11) OXA-48-producing (OXA-48-Kp) isolates occurred in Tzaneio Hospital in 2012 and was contained until 2014, when OXA-48-Kp reemerged. The present study involved 19 bloodstream infection (BSI) OXA-48-Kp isolates recovered from 19 intensive care unit (ICU) patients hospitalized between August 2014 and July 2016. MICs were determined by broth microdilution. Beta-lactamase genes were detected by P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 50 publications
4
35
0
Order By: Relevance
“…ST101/OXA-48 has been frequently reported, and in an 11-year epidemiology study of OXA-48 producers among European and north-African countries, a quarter of the OXA-48 K. pneumoniae isolates belonged to ST101 (Potron et al, 2013). Outbreaks of ST101/OXA-48 were also described, with reports from Spain (Pitart et al, 2011;Cubero et al, 2015), Algeria (Loucif et al, 2016), Czech Republic (Skálová et al, 2016) and Greece (Avgoulea et al, 2018). The challenging phenotypic detection of OXA-48 carbapenemases and the rapid horizontal transfer of OXA-48-encoding plasmids favor hospital outbreaks linked to patient transfer (Skálová et al, 2016) and draw attention to the need for continuous and meticulous surveillance, as well as timely investigation.…”
Section: Discussionmentioning
confidence: 99%
“…ST101/OXA-48 has been frequently reported, and in an 11-year epidemiology study of OXA-48 producers among European and north-African countries, a quarter of the OXA-48 K. pneumoniae isolates belonged to ST101 (Potron et al, 2013). Outbreaks of ST101/OXA-48 were also described, with reports from Spain (Pitart et al, 2011;Cubero et al, 2015), Algeria (Loucif et al, 2016), Czech Republic (Skálová et al, 2016) and Greece (Avgoulea et al, 2018). The challenging phenotypic detection of OXA-48 carbapenemases and the rapid horizontal transfer of OXA-48-encoding plasmids favor hospital outbreaks linked to patient transfer (Skálová et al, 2016) and draw attention to the need for continuous and meticulous surveillance, as well as timely investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The presence and nature of carbapenemase determinants was determined by molecular testing of bacterial isolates using either PCR-based platforms (Xpert-CarbaR, Cepheid, Toulouse, France; Allplex, Seegene Inc, Seoul, Korea) or lateral flow immunochromatography systems (Resist-5 OOKNV, CorisBio, Gembloux, Belgium ). Whole genome sequencing (WGS) was performed on BSI isolates as described previously [3]. BSI: bloodstream infection; NDM-CRE: New Delhi metallo-beta-lactamase-producing carbapenem-resistant Enterobacterales.…”
Section: Microbiological Investigationmentioning
confidence: 99%
“…K.pneumoniae ST101 is known as hypervirulent clone mostly responsible for pneumonia and bacteremia in intensive care units. (30, 31). In our study, ColR-HvKP ST101 isolates were found to be associated with VAP infections (p=0.009).…”
Section: Discussionmentioning
confidence: 99%